Serum follicle-stimulating hormone levels predict time to development of castration resistant prostate cancer - Siemens, David Robert; Hoare, Dylan; Skinner, Tom; Black, Angela (Canadian Urological Association Journal, 2015)
Introduction: Treatment of advancing prostate cancer focuses on blocking the activation of the androgen receptor with resultant prolonged perturbation of the hypothalamic-pituitary-gonadal axis. Androgen deprivation therapy (ADT) is marked, however, by eventual progression to castration- resistant prostate cancer (CRPC). Emerging evidence has postulated that follicle-stimulating hormone (FSH) may lead to proliferative and mutagenic responses of prostate cancer. We investigated the association of serum FSH and time to castration resistance. Methods: This was a single-centre retrospective study assessing serum FSH levels of patients undergoing ADT for advancing prostate cancer. The primary outcome was time of ADT initiation to the development of CRPC. For each patient on treatment and with castrate levels of testosterone, the maximum FSH value between ADT commencement and CRPC was identified and recorded. FSH was analyzed as a continuous and categorical variable. Cox multivariate regression in a step-wise fashion was used to explore the association between FSH levels and time to CRPC. Results: From a database of 323 prostate cancer patients actively managed with ADT, 103 men had a documented FSH value while castrate, with 45 men progressing to CRPC. The mean ± standard deviation maximum FSH value of these patients was 6.66 ± 4.22 mIU/mL (range: 1.5–28.1). The mean duration from ADT commencement to CRPC was 3.03 ± 0.34 years (range: 0.36–9.71). Univariate analysis suggested a trend of a negative correlation between FSH values and time to castrate resistance. A FSH value of less than or equal to the lowest tertile (4.8 mIU/mL) was associated with a longer time to CRPC (hazard ratio 0.46; p = 0.006). In the Cox regression analysis, elevated FSH was associated with a shorter duration time to CRPC (p = 0.03). Conclusions: This retrospective, single-centre study would suggest there may be an association between serum FSH levels and time to CRPC for men treated palliatively with ADT for advancing prostate cancer. Further clinical investigation in a larger cohort of men is required to determine any clinical utility of FSH as a biomarker of progression or target for therapy.